Optimalisasi PROACTING (Program Atasi dan Cegah Stunting) Menggunakan Bahan Pangan Lokal di Nagari Pilubang Padang Pariaman - Wahyuni, Fitri; Leovita, Angelia; Rahmayanti, Rini; Gimnastiar, Fajar (CV Firmos, 2026)
Posyandu plays an essential role in providing primary health services, particularly for pregnant women, breastfeeding mothers, infants, and toddlers in stunting prevention efforts. However, an initial assessment in Nagari Pilubang, Sungai Limau District, revealed that the role of Posyandu cadres was not yet optimal due to limited knowledge among cadres and mothers regarding stunting prevention through local food utilization. To address this issue, the Community Partnership Empowerment Program (PKM) was implemented to empower Posyandu cadres in improving health services for pregnant women and toddlers by optimizing local food-based interventions to prevent nutritional problems, especially stunting. The program was conducted over eight months through stages of socialization, training, mentoring, technology application, evaluation, and sustainability. The results showed a significant improvement in cadres’ skills, with 80–85% showing increased post-test scores compared to pre-test. Observations and field practice revealed enhanced knowledge of stunting and nutrition, improved ability to select and utilize local foods, practical skills, communication, leadership, and cadre independence. The program outputs included local food processing products, training modules, intellectual property rights (IPR), scientific publications, and media dissemination. With ongoing collaboration with the Public Health Center and the Health Office, this program is expected to be replicated in other Posyandu across Padang Pariaman Regency.